2001
DOI: 10.1136/bmj.323.7313.593
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of persistent postnatal urinary and faecal incontinence: randomised controlled

Abstract: Objectives To assess the effect of nurse assessment with reinforcement of pelvic floor muscle training exercises and bladder training compared with standard management among women with persistent incontinence three months postnatally. Design Randomised controlled trial with nine months' follow up. Setting Community intervention in three centres (Dunedin, New Zealand; Birmingham; Aberdeen). Participants 747 women with urinary incontinence three months postnatally, allocated at random to intervention (371) or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
300
0
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(318 citation statements)
references
References 20 publications
3
300
0
15
Order By: Relevance
“…As with any behavioural intervention particularly in asymptomatic primigravidae, compliance and dropouts are problematic. Large dropout rates have been noted in similar studies in pregnancy 14,26,27 . However, the unwillingness of some patients to undergo investigations (perineal ultrasound, perineometry and pad test) was disappointing as regular contact was provided.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As with any behavioural intervention particularly in asymptomatic primigravidae, compliance and dropouts are problematic. Large dropout rates have been noted in similar studies in pregnancy 14,26,27 . However, the unwillingness of some patients to undergo investigations (perineal ultrasound, perineometry and pad test) was disappointing as regular contact was provided.…”
Section: Discussionmentioning
confidence: 63%
“…There is good evidence that postnatal pelvic floor exercises are effective in the treatment of postpartum stress incontinence 7,13,14 . Few studies exist using antenatal pelvic floor exercises 15,16 despite the possibility that these might be effective in preventing postnatal stress incontinence 5 .…”
Section: Introductionmentioning
confidence: 99%
“…요실금 발생은 모든 문헌에서 측정되었고, 대변실금은 5개 문헌 (Bø & Haakstad, 2011;Glazener et al, 2005;Glazener et al, 2001;Sleep & Grant, 1987;Wilson & Herbison, 1998 케겔요법 후 질 회음근 수축력은 4개 문헌 (Møkved & Bø, 2000;Møkved et al, 2003;Reilly et al, 2002;Wilson & Herbison, 1998 …”
Section: 임신 및 출산여성에게 시행된 케겔운동에 대한 근거평가에 선택unclassified
“…Long-term follow up was undertaken only in three trials [7][8][9]. None of these studies found a significantdifference long-term in prevalence rates of incontinence between the PFMT and control groups.…”
Section: Boyle Et Al [1]mentioning
confidence: 99%